EFFECT OF INSULIN ADMINISTRATION DURING LUTEAL PHASE ON PROGESTERONE PROFILE AND CONCEPTION RATE IN BUFFALOES (BUBALUS BUBALIS) - HUQ, Q I; GUPTA, H P; PRASAD, SHIV; GUPTA, A K (The Indian Journal of Animal Reproduction, 2023)
The present study was conducted to test the effect of insulin administration (Human Mixtard®, S/C@ 0.25IU/kg body weight} during luteal phase on serum progesterone profile and conception rate in buffaloes. Estrus wasinduced using 2ml (263μg/ml) cloprostenol sodium (im). Buffaloes were bred naturally during estrus. Insulin wasinjected on day 10 of estrous cycle in treatment group (n=10), while PBS was given s/c to the control group (n=1 O)on same day. The conception rate was higher in the treatment group (70%) than the control group (50%}. Theserum progesterone concentration remained higher from day 12 to 30 in the treatment group than the control groupand in pregnant than non-pregnant animals. Thus, it may be concluded that the insulin administration during lutealphase had beneficial effect on the serum progesterone concentration and conception rate.
Keywords: Buffalo; Insulin; Progesterone; Conception rate